Myofibre Hypertrophy in the Absence of Changes to Satellite Cell Content Following Concurrent Exercise Training in Young Healthy Men - Shamim, Baubak; Camera, Donny M.; Whitfield, Jamie (Frontiers in Physiology, 2021)
Concurrent exercise training has been suggested to create an ‘interference effect’, attenuating resistance training-based skeletal muscle adaptations, including myofibre hypertrophy. Satellite cells support myofibre hypertrophy and are influenced by exercise mode. To determine whether satellite cells contribute to the ‘interference effect’ changes in satellite cell and myonuclear content were assessed following a period of training in 32 recreationally active males (age: 25±5 y; body mass index: 24±3 kg·m-2; mean±SD) who undertook 12-wk of either isolated (3 d·w-1) resistance (RES; n=10), endurance (END; n=10), or alternate day (6 d·w-1) concurrent (CET, n=12) training. Skeletal muscle biopsies were obtained pre-intervention and after 2, 8, and 12 wk of training to determine fibre type-specific cross-sectional area (CSA), satellite cell content (Pax7+DAPI+), and myonuclei (DAPI+) using immunofluorescence microscopy. After 12 wk, myofibre CSA increased in all training conditions in type II (P = 0.0149) and mixed fibres (P = 0.0102), with no difference between conditions. Satellite cell content remained unchanged after training in both type I and type II fibres. Significant correlations were observed between increases in fibre type-specific myonuclear content and CSA of Type I (r = 0.63, P < 0.0001), Type II (r = 0.69, P < 0.0001), and mixed fibres (r = 0.72, P < 0.0001). Resistance, endurance, and concurrent training induce similar myofibre hypertrophy in the absence of satellite cell and myonuclear pool expansion. These findings suggest that myonuclear accretion via satellite cell fusion is positively correlated with hypertrophy after 12 wk of concurrent training, and that individuals with more myonuclear content displayed greater myofibre hypertrophy.